THE PREPARATION OF AN IODATE SELECTIVE ELECTRODE USING SILVER IODATE AS THE ACTIVE AGENT IN A CHITOSAN SUPPORT - Ani Mulyasuryani; Qonitah Fardiyah; Rizki Sugiri (Indonesian Journal of Chemistry, 2007)
The iodate-selective electrode based on the principle of precipitation reaction could be made by coating the platinum wire with silver iodate (AgIO3). In this research was carried out optimization the iodate-selective electrode using chitosan membrane as an AgIO3 support. The AgIO3 were added in the 2 mL 1% chitosan solution, is 0.5 to 2.5 % (w/v). The thickness of the membrane used is 6 to 12 µm. The electrode cell potential is measured against Ag/AgCl electrode as a reference electrode. The optimum electrode performance was at 2.0 % of AgIO3 with thickness a membrane of 10 µm. The iodate-selective electrode has a Nernstian factor is 52.96 mV/decade and a response time of 10 seconds. The concentration range was determined from 10-3 M to 10-1 M and the detection limit is 1.12 x 10-5 M.